INTEGRATED STRATEGIES IN THE MANAGEMENT OF TOMATO WILT DISEASE CAUSED BY FUSARIUM OXYSPORUM F. SP. LYCOPERSICI - KUNWAR ZEESHAN KHAN; ABHILASHA A. LAL; SOBITA SIMON (The Bioscan, 2014)
Wilt of tomato (Lycopersicon esculentum) caused by Fusarium oxysporum f. sp. lycopersici (Sacc.) Snyder and Hansen is considered as one of the most devastating disease of tomato both in field as well as green house conditions. In present investigation bio-agents, organic amendment and fungicides were evaluated on different combinations and mode of treatments. In the experiment under field conditions, the treatments are: seedling treatment (ST) of T. harzianum at 100 gl-1 of water, soil application (SA) of FYM at 1000 kgha-1 having T. harzianum at 1 kgq-1 of FYM, ST of P. fluorescens at 100 gl-1 of water, SA of FYM at 1000 kgha-1 having P. fluorescens at 1 kgq-1 of FYM; SA of FYM at 1000 kgha-1; SA of neem oil cake 250 kgha-1 plus FYM 1000 kgha-1; SA of Neem oil cake 250 kgha-1; ST of carbendazim at 1 gl-1 of water and ST of thiram 2 gl-1 of water. Minimum wilt incidence was recorded by soil application of FYM at 1000 kg/ha having T. harzianum at 1 kgq-1 of FYM (4.16 per cent) and maximum disease inhibition percent (94.11 per cent). This treatment also recorded the highest number of branches per plant (16.0), plant height (69.60 cm), highest fruit yield (300.75 q/ha) and increase in fruit yield over the control of 52.87 percent with per rupee return of 4.99.